Study of seismic behavior of recycled aggregate concrete-filled steel tubular columns. (September 2018) - Tang, Yun-Chao; Li, Li-Juan; Feng, Wen-Xian; Liu, Feng; Zhu, Ming
Abstract: This paper discusses the effects of recycled aggregate concrete strength, axial compression ratio, slenderness ratio and steel tube thickness on the seismic performance of recycled aggregate concrete-filled steel tubular columns. The failure process, hysteresis behavior, skeleton curve, stiffness degeneration, ductility coefficient, and energy consumption function were investigated by conducting low cyclic loading test on six recycled aggregate concrete-filled steel tubular columns and two normal concrete-filled steel tubular columns. The finite element method was applied to investigate the effects of slenderness ratio, steel tube thickness, and axial compression ratio on the seismic behavior. A restoring force model for the recycled aggregate concrete-filled steel tubular columns was constructed accordingly and used to compare the experimental and simulated results. The recycled aggregate concrete-filled steel tubular columns showed excellent seismic performance and deformability compared to the normal concrete-filled steel tubular columns, suggesting that they may feasibly and effectively be applied to load-bearing structures in seismic regions. Highlights: The seismic behavior of recycled concrete-filled steel tube columns is analyzed. Finite element method is applied for parameter study. A restoring force model based on simulation results is proposed. The recycled aggregate concrete columns can be effectively used in load-bearing structures.